Importance of international relations for the promotion of renewable energy, preservation of natural resources and environment: Empirics from SEA nations. (August 2022) - Lei, Xiying; Alharthi, Majed; Ahmad, Ishtiaq; Aziz, Babar; Abdin, Zain ul
Abstract: This study develops a relationship between renewable energy, natural resources, and the environment by highlighting the importance of international relations at the regional level. For an econometric analysis, panel data from 1990 to 2020 is examined. The second generation of the Auto Regressive Distributed Lag model is employed to highlight the importance of international relations among the nations and the importance of those relations for the promotion of renewable energy across the region. The findings show that renewable energy is a significant source to improve the environmental quality by controlling carbon emissions. The natural resources in the form of fossil fuels are increasing carbon emissions and rising the severity of environmental issues. The importance of international relationships is determined through an interaction term. The results show that the countries with strong international relationships have a higher ability to adopt such policies that may helpful for the promotion of renewable energy. Therefore, the present study concludes that international relations between the countries are essential to lower the burden on natural resources, and a uniform transition from nonrenewable to renewable energy sources in Southeast Asian countries. The study concludes that the strong international relationship between the countries may act as a catalyst to control carbon emissions through the promotion of renewable energy, and wise use of natural resources at the regional level. Highlights: Renewable energy resources are helping to control environmental issues in SEA countries. Renewable energy helps to lessen the burden on natural resource consumption. Strong international relationships help to promote renewable energy at a regional level. Massive consumption of natural resources increases environmental challenges. The strong international relation for the promotion of renewable energy is inevitable to control carbon emissions.